Teaching activity in the digital environment of the university - Margarita V. Selezneva; Victoriya Yu. Aksenova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The rapid spread of information technologies that radically influence our life and educational space, the change in the structure of needs and activities as a psychological consequence of the development of information technologies for a person all these factors entail changes in the roles and functions of the teacher in the new digital environment of the university, sharpen questions about their competence, competitiveness, and improving the quality of education in Russian university. The purpose of this research is to identify empirically the professional and psychological difficulties and problems in the teaching activity of military university staff (n = 100) related to their readiness to transform according to a new standard focused on e-learning. The methodological basis of the study was the theoretical model of the unified information environment of the university (N.V. Tikhomirova). The authors questionnaire of the teacher was used as the research method. During the study, data were obtained on three groups of teachers who differ in their willingness to carry out pedagogical activities in conditions of uncertainty associated with the nature and tasks in the digital environment of the university. Statistical processing of the obtained results using the method of discriminant analysis showed that these groups statistically significantly differ in their potential capabilities, willingness to be subjects of the information educational environment, results and achievements in e-learning. The main internal obstacle/difficulty is the unwillingness to take a position within the information educational environment, lack of understanding of their new role in it, that is, certain problems in professional self-awareness. It was found that the position of the teacher (active, passive or external) is neither related to the teaching experience at university, and to their age, nor to their scientific status and position. The predictor of the effectiveness of the teachers educational activity in the digital environment is military-technical education. The applied aspect of this work is that it makes a certain contribution to the understanding of the difficulties and problems of the university teacher in the conditions of digitalization of education.